Theoretical approaches to forensic entomology: II. Mathematical model of larval development - Zuben, Claudio José von [UNESP]; Bassanezi, R. C.; Von Zuben, F. J. (Wiley, 1998)
The present study represents the sequence of an overall theoretical approach to model phenomena of interest for forensic entomology. In particular in this paper, a mathematical model that describes the larval development is advanced for blowflies, which are usually the first to find a decomposing corpse. Data on development times for stages and instars of blowflies in experimental conditions have become the baseline information often used to estimate the age of maggots by interpolating these data against on-site conditions. This information on larval development is relevant to estimates of post-mortem interval (PMI) in forensic investigations.